The Effect of Okra Powder Fortification on the Proximate Composition and Glycemic Index of Rice as a Low-Sugar Staple Food for Individuals with Diabetes - Nindya Anggiani Sembiring; Doli Fadly Harahap; Syarifah Riska Mela Putri (JURNAL BIOSAINS, 2026)
The number of individuals with diabetes in Indonesia continues to rise, largely due to the habitual consumption of rice with a high glycemic index that triggers blood glucose spikes. Since rice is an essential part of the Indonesian diet, a practical solution is needed to lower its glycemic impact. This study aimed to analyze the effect of okra powder fortification on the proximate composition and glycemic index of rice as a low-sugar staple food for individuals with diabetes. The research was conducted experimentally using a Completely Randomized Design (CRD) with 50 respondents. Treatments included two controls (fasting and rice without okra) and three fortification levels: 5 g, 10 g, and 15 g of okra powder per 100 g of rice. Proximate analysis covered moisture, ash, protein, fat, and carbohydrate content, while sensory evaluation used a hedonic test. Blood glucose levels were measured at 0, 30, 60, 90, and 120 minutes after consumption, and data were analyzed using ANOVA and Duncan’s Multiple Range Test (DMRT). Results showed that rice fortified with 15 g of okra powder had higher viscosity, reduced glucose absorption, and a lower glycemic index. The product was well accepted in taste, though texture refinement is still needed.